Biofertilizer in the control of the nematode Pratylenchus brachyurus in sugarcane crop - Silva, Grasiele Teixeira da; Rios, Anderli Divina Ferreira; Silva, Rafael Matias da; Buso, Wilian Henrique Diniz; Conceição, Denise Rodrigues; Oliveira, Rafaela Santos de (Scientia Agraria Paranaensis, 2020)
Biofertilizers can also be used as plague and disease control agents. The commercial product Microgeo® is a biological biofertilizer rich in microorganisms. Few studies have been carried out to evaluate the interaction between biofertilizer and nematodes. The objective of this study was to evaluate the efficiency of the Microgeo® biological fertilizer to control the nematode Pratylenchus brachyurus in two sugarcane cultivars. The work was carried out in greenhouse conditions with a completely randomized experimental design (DIC), in a triple factorial scheme (2 x 2 x 4), being two types of sugar cane (CTC 04 and CTC 9003), two types of management of the biofertilizer (Management 1: application of the biofertilizer and inoculation of the nematode at 0 days after transplanting (DAT), management 2: application of the biofertilizer and inoculation of the nematode in the roots of the plant 30 days later) and four doses of the liquid biofertilizer Microgeo® (0 L ha‑1; 150 L ha-1; 300 L ha-1; 450 L ha-1), with four replications. 800 specimens of P. brachyurus were inoculated in each experimental plot. The results showed that cultivating CTC 9003 during the conduct of the experiment showed greater susceptibility to the nematode compared to cultivating CTC 04. The biofertilizer Microgeo® showed no curative or preventive effect on the control of the nematode under the conditions of the experiment.